Incorporating Cystatin C to Predict Methotrexate Elimination in Patients with CNS Lymphoma and Suspicious Renal Function - Jason N. Barreto; Allison L. McClanahan; Andrew D. Rule; Carrie A. Thompson; Erin Frazee (Case Reports in Hematology)
High-dose methotrexate (MTX; ≥1 g/m2) is a renally eliminated and nephrotoxic first-line therapy for central nervous system (CNS) lymphoma. Creatinine-based estimation of renal function is the recommended approach to dosing MTX in these cases, but nonrenal determinants of creatinine production and elimination in cancer patients such as malnutrition and cachexia lead to overestimation of glomerular filtration rate (GFR) by this method and a heightened risk for drug toxicity. Serum cystatin C is one of the first readily available, relatively inexpensive, endogenous biomarkers to emerge as a practical adjunct to creatinine for estimation of renal function for drug dosing. In this report, we describe two cases where cystatin C was used in conjunction with creatinine to inform MTX dosing for CNS lymphoma. In both cases, the estimated GFR was nearly 40% lower with the combination of the two biomarkers compared to creatinine-only estimates. Empiric MTX dose reductions as a product of these results likely spared the patients sustained exposure to toxic drug concentrations and facilitated earlier administration of supportive care interventions. Further prospective investigations with validated dosing regimens including cystatin C are warranted for high-dose MTX.